Effect of Computational Method on Accumulated O2 Deficit - Medbø, Jon Ingulf; Welde, Boye (Frontiers in Sports and Active Living, 2022)
The aim of this study was to examine how relationships between exercise intensity and the rate of energy release established in different ways, affect the calculated O2 deficit. Aerobic energy re-lease is readily measured by the O2 uptake, while anaerobic energy release is per defini¬tion inde-pendent of O2 and it is not easily measured, for example in relation to strenuous exercise. We have calculated the accumulated O2 deficit using nine different approaches. 13 moderately trained sub-jects (three women) volunteered to serve as subjects for cycle ergometry. The subjects’ maximal O2 uptake was 2.9 ± 0.6 mmol s–1 (x ± s; 3.9 ± 0.8 L min–1). Our reference method (M0) is based on measuring the steady state O2 uptake at the end of at least ten bouts of 10 min of exercise at con-stant intensity varying between 30–40% of that corresponding to the maximal O2 uptake and up to a power >90% of the maximal O2 uptake, a rather time-consuming method. The outcomes of eight simpler different approaches have been compared with those of the reference method. The main result is that the accumulated O2 deficit calculated depends quite much on the relationship used to how it is calculated. A protocol of stepwise increases in exercise intensity every 4 min appeared to work well. A gross efficiency method was the one performing poorest. Another important result is that at constant power the O2 uptake rose by the duration beyond 4 min of exercise at all powers examined, also at powers well below that corresponding to the lac-tate threshold. Finally, the O2 uptake during loadless pedaling was considerably higher than the resting O2 uptake, and it appeared to follow a cubic function of the pedaling frequency. In conclu-sion, to obtain reliable values of the anaerobic energy release by the accumulated O2 deficit princi-ple, reliable relationships between exercise intensity and O2 demand must be established. In the discussion we also address two possibilities that may deserve further examination.